CRACKING STUDY OF ONYX WASTE PRECAST CONCRETE PANEL WHICH THE SURFACE IS FINISHED WITH 4MM THICKNESS GRINDING - Danang Hadi Nugroho; Edhi Wahyuni Setyowati; Wisnumurti Wisnumurti (Rekayasa Sipil, 2022)
This research is a continuation of a series of research on Tulungagung onyx waste. The large volume of onyx waste in the area around the Tulungagung onyx processing plant is used as a substitute for gravel aggregate in the concrete mixture which is processed into exposed concrete which has high aesthetic value. In this study, a finishing treatment process (panel thickness thinning) was carried out which aims to produce coarse aggregates from the walls of the onyx concrete waste panels as exposed concrete which has high aesthetic value. The researcher wanted to know the cracking behavior of the onyx concrete waste panel walls before and after the finishing process. The test object used is the test object of previous researchers, namely the wall of the onyx waste concrete panel size 80 cm x 40 cm x 6 cm with practical steel reinforcement Ø6 - 100 mm attached, so that in this study the researcher only carried out the finishing treatment of panel thickness thinning, in-plane three-point loading test and took data on the cracks that occurred. The result of the finishing process by grinding of 2 mm shows that the percentage of aggregate is seen on average 1.8% of the total surface area, while for the finishing of 4 mm it shows that the percentage of aggregate is seen on average 35%. No initial cracks were found on the surface of the specimen after grinding 2 mm or 4 mm. The cracks experienced after loading were flexural cracks, where all the samples had only one crack in the direction almost perpendicular to the panel axis. The bending stress that occurs in the panels during the initial cracking of the non-grinding panels, 2 mm grinding panels, 4 mm grinding panels is 4.75 MPa, 4.62 MPa, 4.60 MPa respectively.